On variability and detecting unreliable measurements in animal cystometry - Danziger, Zachary C.; Jaskowak, Daniel (Frontiers in Urology, 2024)
Animal cystometry, a process of infusing fluid into the urinary bladder to evoke reflex contrac ons, is a common way to study the effects of pathology, injury, or experimental therapy on lower urinary tract (LUT) dynamics. By monitoring fluid movement during the cystometric micturi on cycle, one can compute important quan es that indicate the health and func on of the LUT, such as bladder capacity and voiding efficiency. Unfortunately, volume measurements in these difficult studies are o en unpreventably corrupted by noise, leading to uncertainty when es ma ng key cystometric parameters. This work proposes a criterion, based on measurable quan es, that flags micturi on cycles in cystometry studies that are likely to contain large measurement errors, poten ally allowing experimenters to remove them from analysis to obtain a more accurate summary of LUT dynamics. We describe the criterion and use computer simula ons to demonstrate its u lity.